Comparative Study on the Performance of Solar Dryer with Finned Plate Solar Chimney - Gebremicheal Gedion Habtay; Janos Buzas; Istvan Farkas (Jurnal Tekno Insentif, 2022)
ABSTRACT The objective of this study is to investigate the influence of geometrical parameters of a solar chimney, i.e., on the flow channel air gap, on the performance of a solar dryer in terms of thermal efficiency, drying efficiency, and dried product weight loss. Experimental outcomes showed the temperature inside the drying chamber increases as solar intensity increases, while relative humidity decreases. In the study sliced potatoes were selected to be dried. The average collector and chimney efficiency were found to be higher when a 10 cm air gap height was used instead of a 5 cm air gap height. After 8.5 h of drying, the moisture content of the 5 cm and 10 cm chimney air gap height differed by around 28%. Moreover, the temperature of the chimney absorber was found to be between 35.5-81 °C, with an average of 56.6 °C, which is roughly 13% lower than the collector absorber due to the solar chimney’s orientation. ABSTRAK Tujuan dari penelitian ini adalah untuk mengetahui pengaruh parameter geometri cerobong surya, khususnya ketinggian celah udara saluran aliran, terhadap kinerja pengering surya dalam hal ini efisiensi termal, efisiensi pengeringan, dan kehilangan berat produk kering. Hasil pengujian memperlihatkan bahwa temperatur di dalam ruang pengering meningkat seiring dengan meningkatnya intensitas matahari, sementara kelembaban relatif menurun. Dalam penelitian ini, irisan kentang dipilih sebagai objek pengering. Efisiensi kolektor dan cerobong rata-rata lebih tinggi pada kondisi celah udara 10 cm dibandingkan celah udara 5 cm. Setelah 8,5 jam proses pengeringan, kadar air pada kondisi celah udara cerobong 5 cm dan 10 cm berbeda sekitar 28%. Temperatur penyerap cerobong berada diantara 35,5-81 °C, dengan rata-rata 56,6 °C, yang berarti temperaturnya lebih rendah 13% dibandingkan dengan temperatur penyerap kolektor, sebagai akibat adanya orientasi cerobong surya.